1999
DOI: 10.1002/(sici)1097-4547(19990715)57:2<271::aid-jnr13>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent loss and proliferation of astrocytes following lateral fluid percussion brain injury in the adult rat

Abstract: Astrocyte populations were analyzed over a period of 1 month in the hippocampus following lateral fluid percussion (FP) brain injury. Rats (n = 23) were subjected either to a brain injury of moderate severity, or to anesthesia and surgery without injury (n = 7). At 3 days, 1, 2, or 4 weeks postinjury, subgroups of animals were sacrificed and the brains removed and sectioned for histochemical analysis. The density of astrocytes, identified with gold sublimate staining, decreased significantly in the ipsilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Finally, astrocytes, which are a key component of the BBB (Abbott et al, ), have been shown to be decreased in number after LFP injury in the adult rat hippocampus (Hill‐Felberg et al, ; Zhao et al, ), contributing to BBB alteration. Astrocyte loss starts as early as 30 min postinjury and continues until 24 hr (Zhao et al, ).…”
Section: Preclinical Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, astrocytes, which are a key component of the BBB (Abbott et al, ), have been shown to be decreased in number after LFP injury in the adult rat hippocampus (Hill‐Felberg et al, ; Zhao et al, ), contributing to BBB alteration. Astrocyte loss starts as early as 30 min postinjury and continues until 24 hr (Zhao et al, ).…”
Section: Preclinical Observationsmentioning
confidence: 99%
“…Another study focused on later time points and showed that the astrocyte population in the injured hippocampus at 7 days was reduced by 64% of the total population compared with uninjured rats. After 1 month, the astrocyte population is restored to 85%, showing compensation for the earlier cell loss (Hill‐Felberg et al, ).…”
Section: Preclinical Observationsmentioning
confidence: 99%
“…Acute damage progresses to apoptotic and necrotic neuronal death after LFP in rodents and remains detectable for months (Dietrich et al, 1994b;Rink et al, 1995;Hicks et al, 1996;Yakovlev et al, 1997;Bramlett et al, 1997b;Conti et al, 1998;Keane et al, 2001;Bramlett et al, 2002;Raghupathi et al, 2002;Knoblach et al, 2002b). Moreover, glial susceptibility to the pathology associated with LFP has been demonstrated at both acute and chronic time points throughout the brain (Cortez et al, 1989;Hill et al, 1996;Conti et al, 1998;Carbonell et al, 1999;D'Ambrosio et al, 1999;Hill-Felberg et al, 1999;Zhao et al, 2003;Grady et al, 2003). Regional degeneration can be identified by astrocyte, macrophage and microglia activation (Lowenstein et al, 1992;Soares et al, 1995a;Okimura et al, 1996;Bramlett et al, 1997a;Hill-Felberg et al, 1999;Zhao et al, 2003;Grady et al, 2003).…”
Section: Histology/pathophysiologymentioning
confidence: 99%
“…Moreover, glial susceptibility to the pathology associated with LFP has been demonstrated at both acute and chronic time points throughout the brain (Cortez et al, 1989;Hill et al, 1996;Conti et al, 1998;Carbonell et al, 1999;D'Ambrosio et al, 1999;Hill-Felberg et al, 1999;Zhao et al, 2003;Grady et al, 2003). Regional degeneration can be identified by astrocyte, macrophage and microglia activation (Lowenstein et al, 1992;Soares et al, 1995a;Okimura et al, 1996;Bramlett et al, 1997a;Hill-Felberg et al, 1999;Zhao et al, 2003;Grady et al, 2003). The initial increase in neutrophils lining the vasculature spreads into surrounding contused tissue (Soares et al, 1995a), while damage and loss of endothelial cells demonstrate significant alterations to the microvascula-LATERAL FLUID PERCUSSION BRAIN INJURY ture (Balabanov et al, 2001;Lin et al, 2001).…”
Section: Histology/pathophysiologymentioning
confidence: 99%
“…Similarly, unilateral excitotoxic or mechanical lesion of the DG results in a significant increase in proliferating cells on the lesioned side, most of which were located in the granule cell layer and expressed markers of mature granule neurons by 3 weeks after the lesion . After TBI, proliferation of astrocytes and activated microglia within the site of injury and hippocampus has been reported (Giordana et al, 1994;Hill-Felberg et al, 1999;Tzeng and Wu, 1999). Whether these new glial cells derive from the neurogenic regions or from parenchymal precursors remains to be elucidated.…”
Section: Increases In Neurogenesis Following Cns Injurymentioning
confidence: 99%